Perception of midline deviation by laypersons and orthodontists - Cabello-Pérez, Sandra Victoria (2017)
Objective: To compare the perception of the smile midline deviation by laypersons and orthodontists. Material and method: Descriptive and cross-sectional study; in which 102 subjects participated, 60 laypersons and 42 orthodontists, who evaluated the aesthetics of the smile in photos according to the position of the midline, using a visual analog scale from 0-100 mm; for this, a smile photograph of a 17 years old male patient, with optimal occlusion, symmetrical smile midline position centered was modified by creating deviations to the right and left, using the program Adobe Photoshop CS6. Results: For both evaluators, the results for the deviations of 1, 2, 3 and 4 mm to the right and 1 mm to the left were statistically significant (p <0.05) and the results for deviations to the left of 2, 3 and 4 mm and centered position groups were not significant (p>0.05). There are differences in perceptions according to the side where are the deviations. Conclusion: Orthodontists were more critical to show the perception of the aesthetics of the midline deviations compared with laypersons.